Method for preparing zirconium-aluminum-based grinding tool pore-forming agent from fused zirconia corundum brick waste
By preparing the waste of electromelted zirconium corundum bricks as zirconium aluminum-based hollow ball abrasive pore-making agent, the problems of high pollution and high cost of existing pore-making agent materials are solved, and low-cost, environmentally friendly and efficient abrasive pore-making agents are achieved. Production.
Patent Information
- Application Number
- CN202411527058.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
The existing abrasive pore-forming agent materials have high pollution and high cost problems, and have high refractory requirements, making it difficult to effectively utilize cheap renewable resources, affecting environmental protection and economic benefits.
After drying, crushing and mixing the waste of zirconium corundum bricks (AZS), flux is added and a zirconium aluminum-based hollow ball abrasive pore-making agent is prepared by melt blowing.
It realizes a low-cost and moderate refractory pore-making agent for environmentally friendly abrasives, uses cheap zirconium-containing waste materials, lowers production temperature, and meets the requirements of energy conservation and environmental protection.
Smart Images

Figure FT_1 
Figure BDA0005109517860000071 
Figure BDA0005109517860000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of smelting and abrasive tool manufacturing, and specifically relates to a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent by utilizing waste fused zirconium corundum bricks (AZS). Background Art
[0002] In the application of abrasive tool grinding, especially for the processing of some difficult-to-grind materials, in order to make the abrasive tool have better heat dissipation and chip removal, some pore-forming agents (such as refined naphthalene, sulfur, etc.) are often added artificially to change the organization of the abrasive tool, making the abrasive tool organization looser, so as to reduce the defects of burns, grinding cracks, etc. of the processed workpiece. At present, as people pay more and more attention to environmental protection, highly polluting abrasive tool pore-forming agents such as refined naphthalene and sulfur will gradually be eliminated, so the research and development and application of new environmentally friendly pore-forming agents are imminent. In recent years, through the continuous efforts of abrasive tool technology workers, environmentally friendly inorganic materials such as glass hollow balls and alumina hollow balls have gradually been promoted and applied, but in terms of cost, it is generally more than 15,000 yuan / ton, which is obviously very high for ordinary bonded abrasive tools with lower prices (generally priced at 12,000 to 20,000 yuan / ton).
[0003] In addition, the process temperature of ordinary bonded abrasive tools is not high from the manufacturing process point of view. For example, the hardening temperature of resin bonded abrasive tools is generally around 180°C, and the firing temperature of ceramic bonded abrasive tools generally does not exceed 1300°C. Therefore, the refractoriness of the pore-forming material used as the abrasive tool does not need to reach the refractoriness level of refractory materials (the refractoriness of alumina hollow balls and zirconia hollow balls is required to be above 1800°C).
[0004] In summary, it is of certain practical significance to find environmentally friendly pore-forming agents with low cost and low refractoriness. It can not only effectively utilize the existing cheap renewable resources, but also has certain social significance for environmental protection.
[0005] A large amount of zirconium-containing waste is generated during the production and processing of fused zirconium corundum bricks, such as scrapped unqualified products and a large amount of waste generated during cutting and grinding processes. Generally, the zirconium content is 28-32wt%, the aluminum oxide content is 45-47wt%, the silicon dioxide content is 16-18wt%, and the rest is 3-11wt% of a mixture of sodium oxide, potassium oxide, titanium oxide, iron oxide, magnesium oxide and calcium oxide. Because a small amount of impurities are generated during processing, they cannot be reused.
[0006] As a pore-forming agent for abrasive tools, it is generally only required to have a refractoriness of not less than 1300°C; a room temperature compressive strength of >5MPa; an apparent porosity of 55-60%; and a bulk density of 0.5-1.0g / cm 3, and after adding to the abrasive tool, the inherent quality of the original abrasive tool will not be reduced or the grinding performance of the abrasive tool can be effectively improved to meet the requirements. Therefore, the present invention has good feasibility in preparing zirconium-aluminum-based abrasive tool pore-forming agent using electrofused zirconium corundum brick waste.
[0007] At present, similar products on the market, such as refractory hollow alumina balls and zirconia balls, are all produced by high-temperature melting of powders. The method of the present invention, which uses waste fused zirconium corundum bricks (AZS) to prepare zirconium-aluminum-based abrasive tool pore-forming agents, has a lower cost price advantage than using refractory hollow alumina balls and hollow zirconia balls. At the same time, the product prepared by the method of the present invention contains a certain amount of zirconium oxide components, has a phase change toughening mechanism, and can also adjust the toughness of the abrasive tool. At the same time, the reduction in melting temperature also meets the requirements of energy saving, consumption reduction, and green and environmentally friendly production. Summary of the invention
[0008] Based on the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick (AZS) waste. The zirconium-aluminum-based abrasive tool pore-forming agent is prepared by adding a flux to the zirconium-containing waste and adopting a melt blowing method. While improving its physical and chemical properties, it can also be used in the production of grinding tools such as grinding wheels, so that the zirconium-containing waste can be recycled.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] A method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick (AZS) waste comprises the following steps:
[0011] 1) Drying the zirconium-containing waste in a blast drying oven at a temperature of 110 to 150° C. until the moisture content after drying is below 0.3% (mass fraction); the zirconium-containing waste includes residues, waste slag, cutting fine powder, and grinding fine powder in the production of fused zirconium corundum bricks (AZS);
[0012] The waste materials with larger particles such as residual products and waste residues are crushed in multiple stages until all the crushed materials can pass through the 100-200 mesh screen, and then mixed and homogenized with the waste materials with smaller particles such as cutting fine powder and grinding fine powder to obtain zirconium-containing mixed waste for standby use;
[0013] 2) Mixing the zirconium-containing mixed waste material crushed in step 1) with a flux in a ball mill for 1 to 5 hours; and then treating the mixed waste material with a melt-blowing method to obtain a zirconium-aluminum-based hollow ball grinding tool pore-forming agent.
[0014] The melt blowing method involved in the present invention is to put the material into a three-phase electric arc furnace for high-temperature melting within a certain period of time. The three-phase electric arc furnace is a high-temperature electric furnace that converts electrical energy into heat energy through arc discharge to melt the material into a molten state, and then sprays the molten material through a nozzle to form a hollow sphere. This process requires the use of compressed air or oxygen to spray the molten material into small balls. During the blowing process, it is necessary to control the blowing process parameters such as the air or oxygen exhaust volume and pressure of the nozzle to ensure the uniformity of the size and shape of the hollow ball.
[0015] Specifically, the drying time of the zirconium-containing waste in step 1) is 2 to 8 hours, preferably 2 to 5 hours.
[0016] Specifically, the zirconium-containing waste in step 1) has the following main chemical components and contents (by mass percentage): 28-32% zirconium oxide, 45-47% aluminum oxide, 16-18% silicon dioxide, and the rest being a mixture of 3-11% sodium oxide, potassium oxide, titanium oxide, iron oxide, magnesium oxide, and calcium oxide;
[0017] Preferably, in the mixture, the contents (mass percentage) of some components are: Na2O 1.5-1.7%, K2O<0.05%, TiO2<0.15%, Fe2O3<0.35%.
[0018] Specifically, in step 1), the multi-stage crushing adopts a crocodile crusher, a double-roll crusher or a ball mill.
[0019] Specifically, in step 2), the main components and mass ratio of the zirconium-containing mixed waste are as follows: residue: waste slag: cutting fine powder: grinding fine powder = 3-5: 1-2: 10-15: 1.5-3.
[0020] Specifically, in step 2), the amount of flux used is 3-5% of the weight of the zirconium-containing mixed waste.
[0021] Specifically, in step 2), the flux is at least one of potassium feldspar, sodium feldspar, and boron glass.
[0022] Specifically, in step 2), the process steps of the melt blowing method are: placing the mixed material obtained in step 2) into a three-phase electric arc furnace and melting it at a temperature of 1500°C to 1550°C to form a molten liquid, and then spraying the molten material through the nozzle of the three-phase electric arc furnace to form a hollow sphere, and then naturally cooling it to room temperature (25±5°C); the melt blowing time is 4 to 6 hours in total, and compressed air or compressed oxygen is used for spraying during the melt blowing process; during the melt blowing, the nozzle exhaust volume is 6 to 10m 3 / min, the pressure is 0.5 to 1.0 MPa, and the further pressure is preferably 0.6 to 0.8 MPa.
[0023] Furthermore, in step 2), the prepared zirconium-aluminum-based hollow ball grinding tool pore-forming agent is screened, magnetically separated, and classified to obtain a finished product, which is then packaged for later use.
[0024] Furthermore, based on a general inventive concept, the present invention also provides a zirconium-aluminum-based hollow ball grinding tool pore-forming agent prepared by the above method.
[0025] The zirconium-aluminum-based hollow ball grinding tool pore-forming agent prepared by the present invention is a hollow particle with a particle size of 0.2-5.0 mm and a bulk density of 0.42-0.97 g / cm 3 , true density is 3.6~3.8g / cm 3 The integrity rate of the blown balls is 70-90%.
[0026] Furthermore, based on a general inventive concept, the present invention also provides the use of the zirconium-aluminum-based hollow ball abrasive tool pore-forming agent in the preparation of abrasive tools.
[0027] Specifically, the grinding tool is a grinding wheel for grinding aircraft blades.
[0028] The zirconium-aluminum-based hollow ball abrasive tool pore-forming agent prepared by the present invention is an environmentally friendly inorganic material pore-forming agent and has a wide range of uses, such as for preparing ceramic abrasive tools, resin abrasive tools, superhard abrasive tools, coated abrasive tools, etc. It can also be used alone to prepare rubber roller ceramic grinding wheels.
[0029] The present invention provides a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent by using electrofused zirconium corundum brick waste, that is, preparing a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent for preparing abrasive tools by electrofusion method, which has the characteristics of low cost, low refractoriness, and new environmental protection. The zirconium-aluminum-based hollow ball abrasive tool pore-forming agent of the present invention is formed when a high-temperature melt is suddenly dispersed by a high-speed airflow and extremely rapidly cooled.
[0030] As refractory materials, hollow zirconia balls have the following characteristics: 1) hollow zirconia balls and their products have low volume density and heat capacity, which can improve kiln efficiency and shorten production cycle; 2) The refractoriness is greater than 2400℃, and the long-term use temperature can reach 2200℃. The thermal conductivity is about 50% of Al2O3. It is very stable when used in a hydrogen atmosphere, and the service life can be increased by 30-40% when used in a hydrogen medium frequency furnace; 3) Performance of hollow zirconia balls: ZrO2+CaO content>99%; room temperature compressive strength>5MPa; apparent porosity 55-60%; thermal conductivity W / m·K 0.23-0.35; volume density 2.5-3.0g / cm 3 ; Main crystal phase cubic—ZrO2.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The preparation method of the present invention has the following advantages: the raw materials used in the production are recycled zirconium-containing refractory waste (zirconium-containing fused zirconium corundum brick (AZS) waste), and the waste is subjected to a series of treatments to obtain a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent. Assuming that an enterprise produces 2,000 tons of waste per year, if the method of the present invention is used for treatment, 1,600 tons of zirconium-aluminum-based hollow ball abrasive tool pore-forming agent (of which 20% is lost) can be obtained, and at a price of 15,000 yuan per ton, more than 24 million yuan of income can be obtained. At the same time, the raw materials are industrial waste, which is cheap, melts at a lower temperature, and saves energy and reduces consumption. Therefore, the zirconium-aluminum-based hollow ball abrasive tool pore-forming agent has a better cost advantage than the use of refractory hollow alumina balls and hollow zirconia balls. At the same time, the present invention makes the reuse of industrial waste and low-temperature energy saving and environmental protection the highlights of the product development.
[0033] 2. The zirconium-aluminum-based abrasive tool pore-forming agent prepared by the present invention is a hollow zirconium oxide ball pore-forming agent, which can be directly used as a pore-forming material for abrasive tools. When used, the large and small balls can be classified, and hollow balls of different particle sizes can be used according to the requirements of the abrasive tool structure. The maximum use temperature of the zirconium-aluminum-based abrasive tool pore-forming agent can reach 1300°C.
[0034] 3. The zirconium-aluminum-based hollow ball abrasive tool pore-forming agent prepared by the present invention fully meets the requirements of abrasive tool pore-forming agent conditions, has a high porosity, and has high refractoriness. It is environmentally friendly and non-volatile during abrasive tool sintering. The large-pore abrasive tool prepared using it has the advantages of not burning the workpiece, high strength, good shape retention, and high durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a schematic flow chart of the method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent by utilizing electrofused zirconium corundum brick waste. DETAILED DESCRIPTION
[0036] The technical solution of the present application is described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0037] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical content disclosed by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0038] In the following embodiments, the zirconium-containing waste is fused zirconium corundum brick (AZS) waste, which is mainly sourced from waste generated in the production process of fused zirconium corundum brick manufacturers and recycled waste that can no longer be used by fused zirconium corundum brick manufacturers, including residual products, waste slag and solid waste generated in the production of fused zirconium corundum brick (AZS) and cutting fine powder, grinding fine powder and other processing.
[0039] The main components and contents (mass percentage) of the zirconium-containing waste are: 28-32% zirconium oxide, 45-47% aluminum oxide and 16-18% silicon dioxide, and the rest is a mixture of 3-11% sodium oxide, potassium oxide, titanium oxide, iron oxide, magnesium oxide and calcium oxide.
[0040] The main components and mass ratio of the zirconium-containing mixed waste are as follows: residue: waste slag: cutting fine powder: grinding fine powder = 3-5: 1-2: 10-15: 1.5-3.
[0041] The flux is at least one of potassium feldspar, sodium feldspar and boron glass, and its usage is not more than 3-5% of the weight of the zirconium-containing mixed waste.
[0042] When the melt blowing method is used, the melting temperature is 1500℃~1550℃, the melting time is 4~6 hours, and the nozzle exhaust volume is 6~10m 3 / min, the pressure is 0.5-1.0 MPa, and the pressure is preferably 0.6-0.8 MPa.
[0043] The melt blowing method involved in the present invention is to put the material into a three-phase electric arc furnace for high-temperature melting within a certain period of time. The three-phase electric arc furnace is a high-temperature electric furnace that converts electrical energy into heat energy through arc discharge to melt the material into a molten state, and then sprays the molten material through a nozzle to form a hollow sphere. This process requires the use of compressed air or oxygen to spray the molten material into small balls. During the blowing process, it is necessary to control the blowing process parameters such as the air or oxygen exhaust volume and pressure of the nozzle to ensure the uniformity of the size and shape of the hollow ball.
[0044] The three-phase electric arc furnace used in the present invention is a conventional device in the prior art. Its structure is not the inventive point of the present invention, so it will not be described in detail. The other process parameters of the melt blowing method in the present invention can be set conventionally.
[0045] Example 1
[0046] Example 1 provides a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick (AZS) waste, the process is as follows: Figure 1 As shown, the specific steps are as follows:
[0047] 1) Drying the zirconium-containing waste (residues, waste slag, cutting fine powder, and grinding fine powder in the production of fused zirconium corundum bricks) in a blast drying oven at 120° C. until the moisture content after drying is below 0.3% (mass fraction). In Example 1, the drying time is 2 to 5 hours;
[0048] For waste materials with larger particles such as remnants and waste residues, they are crushed by crocodile crushers, roller crushers or ball mills in multiple stages until all the crushed materials can pass through a 100-mesh screen, and then mixed and homogenized with waste materials with smaller particles such as cutting fine powder and grinding fine powder to obtain zirconium-containing mixed waste, which is then bagged and put into use;
[0049] 2) In order to lower the melting temperature, the zirconium-containing mixed waste material crushed in step 1) (whose mass ratio is 3:1:15:3) and flux (potash feldspar, the amount of which is 3% of the weight of the waste material) are mixed evenly in a ball mill, and the mixing time is controlled within 2 hours;
[0050] Then, a hollow ball abrasive tool pore-forming agent is prepared by melt blowing method, and a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent is obtained; the specific process steps are: the mixed material obtained in step 2) is placed in a three-phase electric arc furnace and melted at 1550°C to form a molten liquid, and then the molten material is sprayed through the nozzle of the three-phase electric arc furnace to form a hollow sphere, and then naturally cooled to room temperature (25±5°C); the melt spraying time is 4 hours in total, and compressed air is used for spraying during the melt spraying process; during the melt spraying, the nozzle exhaust volume is 8m 3 / min, the pressure is 0.8MPa.
[0051] Then the prepared zirconium-aluminum-based hollow ball grinding tool pore-forming agent is screened, magnetically separated and classified to obtain a finished product, which is then packaged for later use.
[0052] Example 2
[0053] Example 2 provides a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick (AZS) waste. The process method of Example 2 is different from that of Example 1 in step 2);
[0054] In step 2), the zirconium-containing mixed waste material (whose mass ratio is 5:2:10:2) after crushing in step 1) and flux (including potassium feldspar, sodium feldspar and boron glass, wherein the amount of potassium feldspar is 2% of the weight of the waste material, the amount of sodium feldspar is 2% of the weight of the waste material, and the amount of boron glass is 1% of the weight of the waste material) are mixed evenly in a ball mill, and the mixing time is controlled within 2 hours;
[0055] Then, a hollow ball abrasive tool pore-forming agent is prepared by melt blowing method, and a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent is obtained; the specific process steps are: the mixed material obtained in step 2) is placed in a three-phase electric arc furnace and melted at 1500° C. to form a molten liquid, and then the molten material is sprayed through the nozzle of the three-phase electric arc furnace to form a hollow sphere, and then naturally cooled to room temperature (25±5° C.); the melt spraying time is 4 hours in total, and compressed air is used for spraying during the melt spraying process; during the melt spraying, the nozzle exhaust volume is 10m 3 / min, the pressure is 0.6MPa.
[0056] Then the prepared zirconium-aluminum-based hollow ball grinding tool pore-forming agent is screened, magnetically separated and classified to obtain a finished product, which is then packaged for later use.
[0057] Example 3
[0058] Example 3 provides a method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick (AZS) waste. The process method of Example 3 is different from that of Example 1 in step 2);
[0059] In step 2), the zirconium-containing mixed waste material (whose mass ratio is 4:2:12:2) after crushing in step 1) and flux (including potassium feldspar and sodium feldspar, wherein the amount of potassium feldspar is 2% of the weight of the waste material, and the amount of sodium feldspar is 2% of the weight of the waste material) are mixed evenly in a ball mill, and the mixing time is controlled within 2 hours;
[0060] Then, a hollow ball abrasive tool pore-forming agent is prepared by melt blowing method, and a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent is obtained; the specific process steps are: the mixed material obtained in step 2) is placed in a three-phase electric arc furnace and melted at 1550°C to form a melt, and then the molten material is sprayed through the nozzle of the three-phase electric arc furnace to form a hollow sphere, and then naturally cooled to room temperature (25±5°C); the melt spraying time is 6 hours in total, and compressed air is used for spraying during the melt spraying process; during the melt spraying, the nozzle exhaust volume is 9m 3 / min, the pressure is 0.7MPa.
[0061] Then the prepared zirconium-aluminum-based hollow ball grinding tool pore-forming agent is screened, magnetically separated and classified to obtain a finished product, which is then packaged for later use.
[0062] Performance Testing
[0063] The zirconium-aluminum-based hollow ball abrasive tool pore-forming agents prepared in Examples 1 to 3 were tested for performance indicators (test method reference standards include: GB / T24487-2022, Q / 320282AF003-2020, YB / T4764-2019, Q / OILYSO48-92), and the results are shown in Table 1.
[0064] Table 1
[0065]
[0066] It can be seen from the above data that the particle size of the hollow spheres in Examples 1 to 3 is controlled within the range of 0.2 to 5.0 mm, and their bulk density, true density, and integrity rate of the blown balls are all within the designed range, fully meeting the production requirements of the abrasive tool pore-forming agent, having a high porosity and high refractoriness, and being environmentally friendly and non-volatile during abrasive tool sintering.
[0067] Application Examples
[0068] The zirconium-aluminum-based hollow ball abrasive tool pore-forming agent prepared in Examples 1 to 3 is applied to abrasive tool production, specifically for the production of aircraft blade grinding wheels, the grinding wheel specification model is V-P400x20x127PA / WA80G50m / s, and belongs to a multi-porous abrasive tool (the grinding wheel is prepared according to the method in the reference document "Hou Yonggai, editor-in-chief. Ceramic Abrasive Tool Manufacturing [M]. China Light Industry Press, 2010", and its preparation method is not the inventive point of the present invention, so it is not repeated here). The prepared grinding wheel is subjected to the factory grinding tool rotation strength inspection and user grinding test (the test method refers to the standard GB / T2493-2023 "Grinding Tool Rotation Strength Test Method"), and its performance comparison is shown in Table 2. At the same time, the grinding wheel prepared using refined naphthalene as a pore-forming agent is used as a control group.
[0069] Table 2
[0070]
[0071] The “#” in Table 2 refers to the specification of 0.178~0.284mm.
[0072] From the actual application cases, the rotational rupture strength of the abrasive tool prepared by the zirconium-aluminum-based hollow ball abrasive tool pore-forming agent of Examples 1-3 of the present invention is significantly higher than the strength of the abrasive tool prepared when refined naphthalene is used as a pore-forming agent, and its durability in grinding applications is also significantly increased. At the same time, the surface quality and shape retention of the workpiece are also improved to a certain extent.
[0073] The above embodiments are examples of the implementation methods of the present invention, and the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a zirconium-aluminum-based abrasive tool pore-forming agent using fused zirconium corundum brick waste, characterized in that: The following steps are involved: 1) Drying the zirconium-containing waste at a temperature of 110-150° C. until the moisture content after drying is below 0.3wt%; the zirconium-containing waste includes residues, waste slag, cutting fine powder and grinding fine powder in the production of fused zirconium corundum bricks; The waste materials with larger particles of residual products and waste residues are crushed in multiple stages until all the crushed materials can pass through the 100-200 mesh screen, and then mixed and homogenized with the waste materials with smaller particles of cut and ground fine powder to obtain zirconium-containing mixed waste for standby use; 2) The zirconium-containing mixed waste material crushed in step 1) is mixed with a flux, and the mixing time is controlled to be 1 to 5 hours; and then treated by melt blowing method to obtain a zirconium-aluminum-based hollow ball abrasive tool pore-forming agent.
2. The method according to claim 1, characterized in that The zirconium-containing waste in step 1) has the following main chemical components and mass percentages: 28-32% zirconium oxide, 45-47% aluminum oxide and 16-18% silicon dioxide, and the rest is a mixture of 3-11% sodium oxide, potassium oxide, titanium oxide, iron oxide, magnesium oxide and calcium oxide.
3. The method according to claim 1, characterized in that Step 2) The main components and mass ratio of the zirconium-containing mixed waste are as follows: residue: waste slag: cutting fine powder: grinding fine powder = 3~5:1~2:10~15:1.5~3.
4. The method according to claim 1, characterized in that In step 2), the amount of flux used is 3-5% of the weight of the zirconium-containing mixed waste.
5. The method according to claim 1, characterized in that In step 2), the flux is at least one of potassium feldspar, sodium feldspar and boron glass.
6. The method according to claim 1, characterized in that In step 2), the process steps of the melt blowing method are as follows: the mixed material obtained in step 2) is placed in a three-phase electric arc furnace and melted at a temperature of 1500°C to 1550°C to form a molten liquid, and then the molten material is sprayed through the nozzle of the three-phase electric arc furnace to form a hollow sphere, and then naturally cooled to room temperature; the melt blowing time is 4 to 6 hours in total, and compressed air or compressed oxygen is used for spraying during the melt blowing process; during the melt blowing, the nozzle exhaust volume is 6 to 10m 3 / min, pressure is 0.5~1.0MPa.
7. The method according to claim 6, characterized in that In step 2), during melt blowing, the pressure is 0.6-0.8 MPa.
8. A zirconium-aluminum based hollow ball grinding tool pore forming agent prepared by the process described in any one of claims 1 to 7.
9. Use of the zirconium-aluminum-based hollow ball abrasive tool pore-forming agent according to claim 8 in the preparation of abrasive tools.
Citation Information
Patent Citations
Purification method for abandoned zirconia alumina refractory brick
CN102898161A
Method for producing zirconium-aluminum composite oxide by utilizing waste zirconium-containing refractory material
CN103193266A
Technology for preparing zirconium-aluminium composite powder from AZS solid waste material
CN105236998A
Components of high-stability electric smelting AZS brick
CN106588057A
Ceramically bound porous grinding tool
WO2002007933A1